Universal Child Allocation, living conditions and education. Social policies and educational inclusion in Buenos Aires State - Gluz, Nora Beatriz; Rodriguez Moyano, Inés (Education Policy Analysis Archives, 2013)
The article introduces the results of a study about the Universal Child Allocation (Asignación Universal por Hijo, AUH) ), a social policy measure implemented by the educational system of Buenos Aires State, in Argentina. The article’s goal is to present the different meanings assumed by this measure within the institutional school frames, through the analysis of the AUH  appropriation processes amid the educational context and the school participants. Beyond the big leap that this measure represents in the expansion of rights, the conclusions suggests that the AUH  design preserves the control mechanisms that foster the customary welfare preconceptions, blocking therefore the schooling inclusion processes and the universalist aspirations of policies.